Assessment of sleep quality and its disorders in students at the State University of Mato Grosso do Sul (Research, Society and Development, 2022)
Objective: To evaluate sleep habits and disorders among students from diffrent undergraduate courser at the State University of Mato Grosso do Sul (UEMS), through the application of PSQI and ESE instruments, correlating with sociodemographic data of the students. Methodology: The presente study was carried out in a quantitative, observational, transversal and decriptive way, with a situational analysis of 110 academics, frome the Theater, Tourism, Performing Arts, Dance and Pedagogy courses, through applied questionnaires (sociodemographic, PSQI and Epworth Sleepiness Scale). The data obtained were tabulated and processed using the IBM SPSS Statistics software, being presented in the forme of relative and absolute frequencies. Results: Of the 110 academics, 16 accepted to participate in the research and adequately filled out the questionnaires. Of the total number of participants, 81,25% (n=13) were female. 31,25% (n=5) were from theater course, 31,25% (n=5) were from the tourism course, 25% (n=4) were from the performing arts course, 6,25% (n=1) was from the dance course and 6,25% (n=1) was from the pedagogy course. 62,5% (n=10) of the participants had poor sleep quality, with a PSQI score greater than 5. The assessment of the level of excessive daytime sleepiness according to the ESE (Epworth Sleepiness Scale) indicated that 31,25% (n=5) of the students had excessive daytime sleepiness and 68,75% (n=11) had no disturbances. Conclusion: It was observed that most students had poor sleep quality and most had excessive daytime sleepiness, directly interfering with student’s academic performance.